Thermal and electrical conductivity of carbon nanotube-1-hexadecyl-3-methylimidazolium bromide (CNT-HDMIM[Br]) and carbon nanotube-water (CNT-Water) nanofluids - Yumul, Mariane Duñgo (College of Engineering, University of the Philippines Diliman, 2014)
High performance cooling is one of the top technical challenges of high-tech industries that need to be addressed. As such, preparation of heat transfer fluids with high thermal conductivity to satisfy the requirements of high heat flux applications is indispensible. Nanoparticle fluid suspensions or nanofluids as a new class of nanotechnology-based heat transfer fluids exhibit thermophysical properties such as thermal conductivity superior to conventional fluids and particle fluid suspensions. This study presents the thermal and electrical conductivity of multiwalled carbon nanotubes dispersions in 1-hexadecyl-3-methylimidazolium bromide (HDMIM[Br]) and in water at low particle concentrations. Thermal conductivity measurements were performed using the transient hot-wire technique while the electrical conductivity was measured using a 4-cell conductivity electrode meter with built-in automatic temperature compensation. The results showed a thermal conductivity enhancement of up to 44% for CNT- HDMIM[Br] nanofluids and 15% fir CNT- Wtare nanofluids, bot at a particle concentration of 500pp, (0.62&v/v) at 75°C. Furthemore, the effects of temperature and particle concentration on the thermal conductivity enhancement and on the electrical conductivity were investigated. Empirical models were also presented to describe the relationship and effects of these parameters to the thermal conductivity enhancement.